Fluorine containing latex coatings prepared using phosphazene-based flame retardant as an efficient crosslinking agent - Rückerová, Adéla; Machotová, Jana; Medunová, Michaela; Puková, Kateřina; Kalendová, Andréa (University of Pardubice, 2018)
The paper is focused on the use of phosphazene derivative in latex coatings. Hexaamino-cyclo-triphosphazene can act as a low-molecular-weight hardening agent for latex copolymers if the shell structure of latex particles contains molecules of glycidyl methacrylate. The coatings containing the fluorine atoms and hexaamino-cyclo-triphosphazene exhibited transparent character, high gloss and convenient mechanical properties. The incorporated phosphazene caused the increase of heat resistance of coatings in terms of the decrease of the heat emission during the material combustion.
Keywords: core-shell; phosphazene; cone-calorimeter; emulsion polymerization